KEBIJAKAN PENEGAK HUKUM DALAM PENANGGULANGAN TINDAK PIDANA PERJUDIAN MELALUI MEDIA ELEKTRONIK DI INDONESIA - Anggada Perkasa; Kartina Pakpahan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This research aims to analyze criminal law enforcement policies in combating cyber gambling offenses in Indonesia. Through a normative legal approach and qualitative research, this study refers to legal norms found in legislation and relevant literature materials. The research findings indicate that law enforcement policies in combating cyber gambling offenses require the codification and unification of legal fields, as well as the development of new legislation. These legal instruments are crucial in supporting development in various sectors, in line with the demands of development, legal awareness, and societal perspectives on behavioral assessments. The application of criminal sanctions against perpetrators of gambling offenses utilizes the general minimum and specific maximum systems. However, within this framework, judges do not have full discretion in determining the appropriate type of punishment for the offenders. Instead, they must adhere to the criminal penalty provisions established in the legislation. In conclusion, regulating cyber gambling offenses within the legal framework in Indonesia requires an improvement in the quality and quantity of investigators specializing in Information Technology and Electronics (ITE) at both the National Police Headquarters and Regional Police Offices. Investigators face challenges in identifying online gambling agents who use false identities and effectively apprehending and detaining offenders.